Thermal Effect of Thermal Energy Storage (TES) Tank for Solar Energy Application During Charging Cycle Based on the Grid Sensitivity Analysis - Tanti, Ali; Norfadzilah, Jusoh; R. A., Bakar; Teoh, S. J.; K., Kadirgama (Elsevier Ltd, 2015)
Present design and engineering processes often rely on the simulation tools as the preliminary assessment or verification process of development. This is due to computational tools are naturally augmented by the sensitivity and uncertainty. As from the incomplete understanding of the input parameters, it is important and necessary to judge the reliability of the results. This is where the grid sensitivity play the role as the point of reference, verification and evaluation data. In this paper investigate the effect of grid sensitivity analysis based on level of mesh to the thermal effect of thermal energy storage (TES) tank for solar energy application during charging cycle. The experiment was performed with TES tank is using water as the working fluid and operated for 9 hours from 9 am to 6 pm with the volume flow rate of 13.2 L/min. The experiment resulted the temperature TES outlet is in the range of 45 to 65 °C. The experimental data is used in the simulation and the results is compared and discussed. The grid sensitivity analysis based on different level of mesh is simulated using CFD flow simulation. The simulation resulted the best initial mesh level to compare with experimental results is mesh level 5. The comparison of experimental and simulation using initial mesh level 5 resulted the percentage difference of 9.67%. In conclusion, the grid sensitivity analysis not only affect the thermal behaviour of the TES tank but also the computational time.